CONTENT ANALYSIS OF CIGARETTE PACKS IN INDONESIA: REGULATORY NON- COMPLIANCE AND PRODUCT PROMOTION ADVANTAGE - Mouhamad Bigwanto; Widyastuti Soerojo (Public Health of Indonesia)
Background: A cigarette pack is the most intimate property and frequently seen by smokers every time they want to start smoking. It gives tobacco industry the opportunity to scrutinize every single space including the inside part of the pack to promote tobacco product and it is often called a mini billboard.